Conflict of Palm Oil Companies with Indigenous People and Forest Surrounding Society - Herningtyas, Wieke (BHUMI: Jurnal Agraria dan Pertanahan, 2021)
Abstract: Oil palm was one of profitable industrial crops. Oil palm high demand in industries encouraged new plantation field opening as oil palm plantation by means of forest conversion method. From land acquisition to oil palm plantation management, tenurial conflict often occurs. This article aimed to map some existing researches concerning conflict of palm oil companies with indigenous and surrounding forest community in Indonesia. This article uses systematic review method by using conflict-related keywords as assisting tool in filtering the data in order to acquire matching articles. Conflict of palm oil companies with indigenous people and surrounding forest community was distributed into four types. Type 1 was the conflict related to land acquisition and HGU permit. Type 2 was the conflict related to plasma plantation development and land compensation which would be used for plasma plantation. Type 3 was the conflict related to Broken Promises and Unfulfilled CSR Commitment. Type 4 was the conflict which occurred during plasma plantation management by cooperatives and companies for oil palm production (TBS and CPO). Keywords: conflict, plantation, palm oil, indigenous people, people surrounding society Intisari : Kelapa sawit merupakan salah satu produk tanaman industri yang menguntungkan. Tingginya permintaan kelapa sawit oleh pasar industri mendorong pembukaan lahan perkebunan baru untuk perkebunan kelapa sawit melalui konversi hutan. Konversi lahan sering terjadi konflik tenurial. Artikel ini bertujuan untuk memetakan penelitian-penelitian terdahulu mengenai konflik antara perusahaan perkebunan kelapa sawit dengan masyarakat adat/masyarakat sekitar hutan di Indonesia. Penelitian ini menggunakan metode sistematik review dengan menggunakan kata kunci sebagai alat bantu dalam proses penyaringan untuk mendapatkan artikel yang sesuai. Konflik antara perusahaan perkebunan kelapa sawit dengan masyarakat adat/masyarakat sekitar hutan dibagi menjadi empat tipe. Tipe 1 adalah konflik terkait akuisisi lahan dan perizinan HGU. Tipe 2 adalah konflik yang terjadi terkait pengembangan perkebunan plasma dan ganti rugi lahan yang akan digunakan untuk perkebunan plasma. Tipe 3 adalah konflik yang terjadi terkait janji yang tidak ditepati dan komitmen dari CSR yang tidak dipenuhi. Tipe 4 adalah konflik yang terjadi dalam pengelolaan kebun plasma oleh koperasi dan perusahaan untuk menghasilkan kelapa sawit (TBS dan CPO). Kata Kunci: kelapa sawit, konflik, masyarakat adat, masyarakat sekitar hutan perkebunan